Chronicle of the First China Animal Law Forum - Beijing, July 2019 - Bo Li (Derecho Animal, 2019)
On July 11 and 12, 2019 the First China Animal Law Forum was held in Beijing, which was co-hosted by the Capital Animal Welfare Association and the Vshine Animal Protection Association. Over 130 people from mainland China, Hong Kong, USA and Africa took part in the forum, including professionals, lawyers, government, NGO, animal protection volunteers and others. The main topic was how to use laws creatively to protect animals.